P463 Long-term effects of anti-TNF therapy on bone metabolism. (16th January 2018) - O'Morain, N; Farrell, G; Hanly, M; Veerappan, S; McNamara, D; Breslin, N; O'Morain, C; Healy, M; Ryan, B
Abstract: Background: Bone loss associated with inflammatory diseases is induced by pro-inflammatory cytokines, which play a major role in decreasing bone mineral density (BMD) and increasing the risk of subsequent osteoporosis. TNFα is an important cytokine in the activated inflammatory cascade, and has been shown to be a potent activator of bone resorption. Anti-TNF therapy (ATT) has been shown to have beneficial effects on bone metabolism in the short-term, but there is a dearth of long-term prospective data. The aim of this study was to evaluate the long-term effects of ATT on bone metabolism. Methods: This retrospective observational cohort study consisted of 37 IBD patients who had participated in a 10-year study previously of anti-TNF therapy (ATT) naïve patients. That study assessed the short-term effects of ATT on bone mineral density by way of DXA scan and metabolic bone markers serum. All participants ( n = 54) of the original study were invited to undergo repeat DXA scanning and collection of blood samples. Blood markers included markers of bone turnover serum type 1 procollagen N-Terminal (P1NP), collagen type 1 cross-linked C-telopeptide (sCTx) and Osteocalcin (OC). Patients were sub-divided for analysis into either a "continue" or "stop" group to assess both long-term effects of ant-TNF therapy and the effect of cessation of therapy on BMD. Wilson–Cox signed-rank test was used to assess statistical differences across the groups. Results: In total, 71% ( n = 37 of 52) patients from the original study were recruited for 10-year follow-up assessment. There were three deaths, five refusals, seven uncontactable. Demographics: 50% female, mean age of 44.5 years (range 27–80), 67% ( n = 29) Crohn's. In total, 54% ( n = 20) continued with ATT and 46% ( n = 17) stopped. The baseline and 10-year mean T -scores were −1.57 (SD ± 1.21) increasing to −0.98 (SD ± 1.24) for patients remaining on ATT ( p = 0.008) and −1.27 (SD ± 1.03) increasing to −0.92 (SD ± 0.89) for those off ATT ( p = 0.31). Overall, mean bone formation markers (OC, P1NP) improved in the continue group with an increase in P1NP of +0.8 ng/ml ( p = 0.76) and +3.3 ng/ml ( p = 0.11) for OC. This was in contrast to a decrease in the stop group of −6.6 ng/ml ( p = 0.64) for P1NP and −1.5 ng/ml ( p = 0.48) for OC. There was a decrease in bone resorption markers (sCTx) in both the continue −0.07 pg/ml ( p = 0.25) and stop groups −0.16 pg/ml ( p = 0.07). Conclusions: In this 10-year follow-up study, results suggest that long-term (>10 years) treatment with anti-TNF therapy has a beneficial effect on bone metabolism, with a statistically significant improvement in T scores, and an improvement in markers of bone formation and a reduction in bone resorption.